RECITATION METHOD AND ITS EFFECT ON STUDENTS’ CREATIVITY IN THE FIELD OF ISLAMIC RELIGION STUDY IN SMP 29 AL-WASHLIAYAH MEDAN - Lubis, Yani (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: One of the teaching methods applied by the teacher to increase students’ creativity is the recitation method. The population of this study was all students who sat in class II SMP 29 Al-Washliyah Medan and the sample of this study was 55 people. The techniques that used in processing data and analyzing the data in this study were to use the Chi Square test (X2) technique or formula and the contingency correlation (KK) data analysis technique. The findings in the results of this study are as follows: the value of the research price is greater than the critical value or price, which is 21.07, while the price of the criticism table is 13.3 with a 99% confidence interval and a 1% significance level. And the strength of the influence after being calculated through the Contingency Correlation formula is 0.526, and according to the Contingency Choreal interpretation rules if the value of KK = 0.526 means that the influence strength of variable X on variable Y is moderate.